Efektivitas Metode Bernyanyi dalam Matakuliah Shorof Bagi Mahasiswa Pendidikan Bahasa Arab - Rozy, Moh. Rozy Zamroni; Hariyanto, Nur; Rahmad Hidayatullah (Program Studi Pendidikan Bahasa Arab, 2024)
The problems of learning shorof in terms of media and teaching methods that are less effective are the main basis for this article, so this article explores the effectiveness of the singing method in learning shorof courses for Arabic language education students. In learning Arabic, especially the grammar or shorof aspect, students often face challenges of material complexity and motivation. This research also aims to fill the gap in the literature by investigating the extent to which the use of singing methods can improve student understanding and engagement. The research method in this research is quantitative research using a quasi-experimental approach. The research design used in this study was a nonequivalent control group design (pretest-posttest control group design without randomization). In this design, group subjects are not conducted randomly, for example an experimental class in a particular class with existing or existing students. The results showed that the experimental group who received learning using the singing method showed a significant increase in understanding the material compared to the control group. This is proven by the significance value in the paired sample t-test and the independent sample t test which is 0.00 < 0.05, so this figure shows that the singing method has a significant influence and change on students' vocabulary. These findings indicate that the singing method can be an effective approach in learning shorof courses for Arabic language education students. The practical implication of this research is the importance of including music and singing elements in learning design to increase student effectiveness and engagement in learning Arabic.